Changes in the Number and Morphology of Dendritic Spines in the Hippocampus and Prefrontal Cortex of the C58/J Mouse Model of Autism - Barón-Mendoza, Isabel; Maqueda-Martínez, Emely; Martínez-Marcial, Mónica; De la Fuente-Granada, Marisol; Gómez-Chavarin, Margarita; González-Arenas, Aliesha (Frontiers in Cellular Neuroscience, 2021)
Autism spectrum disorder (ASD) has a broad range of neurobiological characteristics, including alterations in dendritic spines, where approximately 90 percent of excitatory synapses occur. Therefore, changes in their number or morphology would be related to atypical brain communication. The C58/J inbred mouse strain displays low sociability, impaired communication, and stereotyped behavior; hence it is considered among the animal models suitable for the study of idiopathic autism. Thus, this study aimed to evaluate the dendritic spines differences in the hippocampus and the prefrontal cortex of C58/J mice. We found changes in the number of spines and morphology in a brain region-dependent manner: a subtle decrease in spine density in the prefrontal cortex; higher frequency of immature phenotype spines characterized by filopodia-like length or small morphology, and a lower number of mature phenotype spines with mushroom-like or wide heads in the hippocampus. Moreover, an in-silico analysis showed single nucleotide polymorphisms (SNPs) at genes collectively involved in regulating structural plasticity with a likely association with ASD, including MAP1A (Microtubule-Associated Protein 1A), GRM7 (Metabotropic Glutamate Receptor, 7), ANKRD11 (Ankyrin Repeat Domain 11), and SLC6A4 (Solute Carrier Family 6, member 4), which might support the relationship between the C58/J strain genome, an autistic-like behavior, and the observed anomalies in the dendritic spines.